NEPALESE HISTORY IN A EUROPEAN EXPERIENCE: A CASE STUDY IN TRANSCULTURAL HISTORIOGRAPHY. Issue 2 (May 2016) - MICHAELS, AXEL; BAJRACHARYA, MANIK; GUTSCHOW, NIELS; HERREN, MADELEINE; SCHNEIDMÜLLER, BERND; SCHWEDLER, GERALD; ZOTTER, ASTRID
ABSTRACT: In March 2013, a group of German, Nepalese, and Swiss historians, Indologists, and an architectural historian gathered for a workshop in Nepal to develop a new approach to the understanding of South Asian historiography, especially the Nepalese chronicles from the nineteenth century. The outcome is the present collaboratively written article. It is argued that, in the past, the analysis of South Asian historiography has been preoccupied by arguments based on an understanding of history that highlights facts and events. A transcultural and multidisciplinary approach, however, would overcome the common dichotomies of factuality and fictionality, history and myth, or evidence and truth. Recognizing the specificity of South Asian historiography, the article develops an approach to bridge asymmetries and entanglements in the academic use of the past in a way that also opens up a new perspective on Western historiography. By analyzing the religious, spatial, literary, and historical, and contemporary or context‐related aspects of a nineteenth‐century chronicle and by using "fieldwork" as a methodological tool for studying historiography, it is proposed to understand the framing of time and the making of sequences and historical periods as an open process that results in the constant and synchronic creation of chronological spaces.